Nilai Spiritualitas dalam Seni Kaligrafi Ayat Kursi: Studi Living Qur’an - Ady, Khilmi; Mustofa, Ahmad; Nadlir, Muhammad Abu (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
The problem addressed in this study originates from the phenomenon of numerous calligraphers offering products featuring calligraphy of Qur'anic verses, with Ayat Kursi being the most popular among the public. This research area is known as Living Qur'an, which focuses more on the practical role of the Qur'an. In this case, the Qur'an is not only a guide but also used as home decoration in the form of calligraphy. This study employs a qualitative research method with Alfred Schutz's phenomenological approach, specifically in-order-to motive and because motive, to uncover the reasons and purposes behind the installation of Ayat Kursi calligraphy. The research data is collected from observations, interviews, and documentation. This study finds that the people of Magelang Regency have a strong preference for Ayat Kursi calligraphy because it is believed to bring blessings, reflect Islamic identity, and possess the power of prayer. The installation of Ayat Kursi calligraphy in homes serves not only as aesthetic decoration but also as a reminder of Allah's greatness, a source of spiritual protection, and a medium for creating a peaceful atmosphere.